Upregulation of RCAN1 causes Down syndrome-like immune dysfunction. Issue 7 (3rd May 2013) - Martin, Katherine R; Layton, Daniel; Seach, Natalie; Corlett, Alicia; Barallobre, Maria Jose; Arbonés, Maria L; Boyd, Richard L; Scott, Bernadette; Pritchard, Melanie A
Abstract : Background: People with Down syndrome (DS) are more susceptible to infections and autoimmune disease, but the molecular genetic basis for these immune defects remains undetermined. In this study, we tested whether increased expression of the chromosome 21 gene RCAN1 contributes to immune dysregulation. Methods: We investigated the immune phenotype of a mouse model that overexpresses RCAN1. RCAN1 transgenic (TG) mice exhibit T cell abnormalities that bear a striking similarity to the abnormalities described in individuals with DS. Results: RCAN1-TG mice display T cell developmental defects in the thymus and peripheral immune tissues. Thymic cellularity is reduced by substantial losses of mature CD4 and CD8 thymocytes and medullary epithelium. In peripheral immune organs T lymphocytes are reduced in number and exhibit reduced proliferative capacity and aberrant cytokine production. These T cell defects are stem cell intrinsic in that transfer of wild type bone marrow into RCAN1-TG recipients restored medullary thymic epithelium and T cell numbers in the thymus, spleen and lymph nodes. However, bone marrow transplantation failed to improve T cell function, suggesting an additional role for RCAN1 in the non-haemopoietic compartment. Conclusions: RCAN1 therefore facilitates T cell development and function, and when overexpressed, may contribute to immune dysfunction in DS.